Enhancing Resilience in Family Caregivers Using an mHealth App - Smeallie, Eleanor; Rosenthal, Lindsay; Johnson, Amanda; Roslin, Chloe; Hassett, Afton L.; Choi, Sung Won (Applied Clinical Informatics, 2022)
Background We previously developed a mobile health (mHealth) app (Roadmap) to promote the resilience of family caregivers during the acute phases of care in patients undergoing hematopoietic cell transplantation (HCT).Objective This study explored users' perspectives on the uptake of Roadmap's multicomponent features and the app's utility in promoting resilience.Methods Fifteen participants were randomized to the full version of the app that included resilience-building activities and the other 15 were randomized to the control version that included a limited view of the app (i.e., without any resilience-building activities). They were instructed to use the app for 120 days. Semistructured qualitative interviews were then conducted with users as part of an ongoing, larger Roadmap study (NCT04094844). During the interview, caregiver participants were asked about their overall experiences with the app, frequency of use, features used, facilitators of and barriers to use, and their perspectives on its utility in promoting resilience. Data were professionally transcribed, coded, and categorized through content analysis.Results Interviews were conducted with 30 participants, which included 23 females and 7 males. The median age of the population was 58 years (range, 23–82). The four main themes that emerged included app use, ease of use, user experiences, and ability to foster resilience. The subthemes identified related to facilitators (convenience and not harmful), barriers (caregiver burden and being too overwhelmed during the acute phases of HCT care), resilience (optimism/positivity and self-care), and app design improvements (personalization and notifications/reminders).Conclusion The qualitative evaluation provided insights into which components were utilized and how one, or a combination of the multicomponent features, may be enhancing users' experiences. Lessons learned suggest that the Roadmap app contributed to promoting resilience during the acute phases of HCT care. Nonetheless, features that provided enhanced personalization may further improve longer-term engagement.
Keywords: mobile health; mHealth; resilience; psychological; family caregivers; qualitative; research; transplantation; hematopoietic stem cell